Analysis Of The Rectangular And Circular Cylindrical Rc Elevated Water Tank Design According To Eurocode - Tee, Deng Wang (Universiti Sains Malaysia, 2021)
Storage tanks are containers that hold liquids, compressed gases, or mediums used for the short or long-term storage of heat or cold. The tanks can be constructed vertically and horizontally, above ground, semi-underground, and underground, carry static and dynamic loads, under vacuum or overpressure, wind, seismic, and temperature influences. In this project, the elevated tank is designed as a circular cylindrical shape elevated water tank and a rectangular shape. The differences between the reinforcement steel and the volume of concrete will be compared between the two designs. The design parameters considered are as described in the Eurocodes. some variables were considered in the design of an elevated water tank which are the thickness of the wall, the thickness of the base and roof, the depth of the tank, the height of the supporting tower. The wind loads are determined using finite element methods. To assist in design, the ETABS software is applied to design the two elevated water tanks. It was found that the circular cylindrical shape is more stable than the rectangular shape by modelling the model in Etabs with and without wind condition. However, the cost of circular cylindrical shape is 39.47 % more than the rectangular shape tanks..